Bathymetric survey and performance of a waste stabilization ponds system - Sánchez, Iván; Matsumoto, Tsunao (Revista de Ciencias Agrícolas, 2013)
Wastewater treatment is an important action for reducing the environmental impacts on receiving water bodies. Stabilization ponds are natural systems widely used for treatment of different kind of effluents, especially in developing countries. The main objective of this work was to diagnose the sludge accumulation and the performance of the sewage treatment plant (STP) of Sao Joao de Iracema city. By means of a batimetric study of anaerobic and facultative lagoons it was determined the sludge accumulation profiles; different water quality parameters on the plant influent and effluent and the influent wastewater flow during 24 consecutive hours were measured in order to monitor the removal efficiency of some water quality parameters. The accumulated sludge volumes represent a 1.87 days reduction of the total hydraulic detention time of the STP; the average efficiency removal of BOD5 was 78.7%, smaller than the minimum efficiency allowed by the Brazilian current legislation; high solids concentrations on the treated liquid were registered and the MPN of faecal coliforms per milliliter on the effluent highly exceeds the maximum allowed values. The STP requires a readjustment on the sand removal pretreatment system, a more effective maintenance and the implementation of a post treatment system to guarantee additional organic matter and fecal coliforms removal in order to adjust the efficiency in accordance to the environmental legislation standards.